2017
DOI: 10.31234/osf.io/2avns
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidental Haptic Sensations May Not Influence Social Judgments: A Purely Confirmatory Replication Attempt of Study 1 by Ackerman, Nocera, & Bargh (2010)

Abstract: This preregistered replication attempt focuses on the finding from Ackerman, Nocera, & Bargh (2010; ANB) that holding a heavy object triggers concepts related to importance. ANB reported that participants who were holding a heavy clipboard rated a job candidate as better overall and more seriously interested in the job than participants holding a light clipboard. We failed to replicate ANB's results; instead, Bayes factor hypothesis tests indicated evidence for the absence of a difference between the heavy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…)。身体化認知とは,認知体験は身体 で体験される感覚や運動に基づいているという考え であり (e.g., Barsalou, 1999;Barsalou, Niedenthal, Barbey, & Ruppert, 2003;Niedenthal, Barsalou, Winkielman, Krauth-Gruber, & Ric, 2005),社会心理学 や認知心理学が中心となって扱ってきたテーマであ る。この考えを支持する知見はたびたび報告されて いる。その中でも有名なものは,温かいもの (マグ カップや袋) を持つと他者の性格を「温かい」と評 価することや向社会的行動を促進するという知見で ある (Williams & Bargh, 2008)。他にも,重いものを 持つと対象の評価が重要性の高い方向にバイアスさ れることが報告されている (Ackerman, Nocera, & Bargh, 2010;Jostmann, Lakens, & Schubert, 2009)。しか しながら,これらの知見に関する多くの直接的追試 は失敗し ている (Beek et al, 2018;Chabris, Heck, Mandart, Benjamin, & Simons, 2019;Ebersole et al, 2016;Lynott et al, 2014;Rabelo, Keller, Pilati, & Wicherts, 2015 Casasanto & Dijkstra, 2010;Marmolejo-Ramos, Elosúa, Yamada, Hamm, & Noguchi, 2013;Meier & Robinson, 2004;Kato, Imaizumi, & Tanno, 2018;Sasaki, Seno, Yamada, & Miura, 2012;Sasaki, Yamada, & Miura, 2015)。情動と結びついている のは上下空間だけではない。左右空間も情動の快不 快と連合している (水平情動メタファ)。水平方向の 連合は利き手依存であることが示されている (e.g., Casasanto, 2009;Casasanto & Chrysikou, 2011;Casasanto & Henetz, 2012;Casasanto & Jasmin, 2010;de la Vega, de Filippis, Lachmair, Dudschig, & Kaup, 2012;de la Vega, Dudschig, de Filippis, Lachmair, & Kaup, 2013) (Brouillet, Milhau, & Brouillet, 2015;Casasanto & Chrysikou, 2011;de la Fuente et al, 2017;Kominsky & Casasanto, 2013) Casasanto (2009) Present study Non Sig.…”
unclassified
“…)。身体化認知とは,認知体験は身体 で体験される感覚や運動に基づいているという考え であり (e.g., Barsalou, 1999;Barsalou, Niedenthal, Barbey, & Ruppert, 2003;Niedenthal, Barsalou, Winkielman, Krauth-Gruber, & Ric, 2005),社会心理学 や認知心理学が中心となって扱ってきたテーマであ る。この考えを支持する知見はたびたび報告されて いる。その中でも有名なものは,温かいもの (マグ カップや袋) を持つと他者の性格を「温かい」と評 価することや向社会的行動を促進するという知見で ある (Williams & Bargh, 2008)。他にも,重いものを 持つと対象の評価が重要性の高い方向にバイアスさ れることが報告されている (Ackerman, Nocera, & Bargh, 2010;Jostmann, Lakens, & Schubert, 2009)。しか しながら,これらの知見に関する多くの直接的追試 は失敗し ている (Beek et al, 2018;Chabris, Heck, Mandart, Benjamin, & Simons, 2019;Ebersole et al, 2016;Lynott et al, 2014;Rabelo, Keller, Pilati, & Wicherts, 2015 Casasanto & Dijkstra, 2010;Marmolejo-Ramos, Elosúa, Yamada, Hamm, & Noguchi, 2013;Meier & Robinson, 2004;Kato, Imaizumi, & Tanno, 2018;Sasaki, Seno, Yamada, & Miura, 2012;Sasaki, Yamada, & Miura, 2015)。情動と結びついている のは上下空間だけではない。左右空間も情動の快不 快と連合している (水平情動メタファ)。水平方向の 連合は利き手依存であることが示されている (e.g., Casasanto, 2009;Casasanto & Chrysikou, 2011;Casasanto & Henetz, 2012;Casasanto & Jasmin, 2010;de la Vega, de Filippis, Lachmair, Dudschig, & Kaup, 2012;de la Vega, Dudschig, de Filippis, Lachmair, & Kaup, 2013) (Brouillet, Milhau, & Brouillet, 2015;Casasanto & Chrysikou, 2011;de la Fuente et al, 2017;Kominsky & Casasanto, 2013) Casasanto (2009) Present study Non Sig.…”
unclassified
“…)。身体化認知とは,認知体験は身体 で体験される感覚や運動に基づいているという考え であり (e.g., Barsalou, 1999;Barsalou, Niedenthal, Barbey, & Ruppert, 2003;Niedenthal, Barsalou, Winkielman, Krauth-Gruber, & Ric, 2005),社会心理学 や認知心理学が中心となって扱ってきたテーマであ る。この考えを支持する知見はたびたび報告されて いる。その中でも有名なものは,温かいもの (マグ カップや袋) を持つと他者の性格を「温かい」と評 価することや向社会的行動を促進するという知見で ある (Williams & Bargh, 2008)。他にも,重いものを 持つと対象の評価が重要性の高い方向にバイアスさ れることが報告されている (Ackerman, Nocera, & Bargh, 2010;Jostmann, Lakens, & Schubert, 2009)。しか しながら,これらの知見に関する多くの直接的追試 は失敗し ている (Beek et al, 2018;Chabris, Heck, Mandart, Benjamin, & Simons, 2019;Ebersole et al, 2016;Lynott et al, 2014;Rabelo, Keller, Pilati, & Wicherts, 2015 Casasanto & Dijkstra, 2010;Marmolejo-Ramos, Elosúa, Yamada, Hamm, & Noguchi, 2013;Meier & Robinson, 2004;Kato, Imaizumi, & Tanno, 2018;Sasaki, Seno, Yamada, & Miura, 2012;Sasaki, Yamada, & Miura, 2015)。情動と結びついている のは上下空間だけではない。左右空間も情動の快不 快と連合している (水平情動メタファ)。水平方向の 連合は利き手依存であることが示されている (e.g., Casasanto, 2009;Casasanto & Chrysikou, 2011;Casasanto & Henetz, 2012;Casasanto & Jasmin, 2010;de la Vega, de Filippis, Lachmair, Dudschig, & Kaup, 2012;de la Vega, Dudschig, de Filippis, Lachmair, & Kaup, 2013) (Brouillet, Milhau, & Brouillet, 2015;Casasanto & Chrysikou, 2011;de la Fuente et al, 2017;Kominsky & Casasanto, 2013) Casasanto (2009) Present study Non Sig.…”
unclassified
“…In neither of the studies, they found evidence that physical warmth leads to interpersonal warmth. Furthermore, also the findings of the weightimportance relationship were not reproduced (Beek et al, 2017).…”
Section: Criticism Of Embodied Cognition Researchmentioning
confidence: 94%
“…However, this evidence is not undisputed; a number of replication studies failed to reproduce some of the effects (e.g. Beek et al, 2017;Chabris, Heck, Mandart, Benjamin, & Simons, 2019;Lynott et al, 2014). Currently, authors emphasize the need for further research investigating when and how embodiment occurs (i.e.…”
Section: Embodied Cognitionmentioning
confidence: 99%
See 1 more Smart Citation